A Model to Explore Business Opportunities in Ubiquitous Environments - Franco, Laerte; Rosa, João; Barbosa, Jorge; Costa, Cristiano; Yamin, Adenauer C. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
The mobile and ubiquitous computing has been stimulated by the widespread diffusion of mobile devices, wireless networks, and, more recently, by location systems. In this context, applications are emerging in different areas, such as, education, entertainment, and commerce. The application of the ubiquitous computing in the exploration of business opportunities is called Ubiquitous Commerce. This paper proposes the UbiTrade model, which aims at supporting the ubiquitous commerce. Considering the related works, we can note that the proposed model is the only that allows the user to act either in the supplier role or in the consumer character. In addition, most of the current proposals are restricted to a specific area of business. The UbiTrade does not have this restriction. The model was implemented and its validation was conducted by a group of users. The results indicated the model feasibility, particularly in regard to its most significant contribution, that is, the integration of the support to the roles of supplier and consumer.